Analisis Sistem Pendidikan Tahfidz di Pondok Pesantren Tahfidzul Qur’an Baitul Abidin Darussalam Wonosobo - Dina Lutfa Azizi; Moh. Sakir; Muhtar Sofwan Hidayat (Islah Tarbawi: Journal of Islamic Education and Learning, 2026)
Tahfidz Al-Qur'an education plays an important role in preserving the authenticity of the Qur'an through a structured and continuous learning process. The success of tahfidz education is determined not only by students' ability to memorize the Qur'an but also by the educational system that encompasses curriculum, learning methods, and evaluation. This study aims to analyze the tahfidz education system at Pondok Pesantren Tahfidzul Qur'an (PPTQ) Baitul Abidin Darussalam Wonosobo, focusing on its curriculum, learning methods, and evaluation system. This research employed a qualitative approach with a field research design. Data were collected through observation, interviews, and documentation involving the head of the pesantren, curriculum board members, teachers, and administrators as research subjects. Data validity was ensured through source triangulation and technique triangulation. The findings reveal that: (1) the tahfidz curriculum is designed through the integration of tahsin, tahfidz, muroja'ah, and diniyah education activities supported by memorization targets adjusted to students' educational levels; (2) the learning methods applied consist of talaqqi, tikrar, and muroja'ah, which are implemented in memorization addition, memorization submission, and memorization maintenance activities; and (3) the evaluation system is conducted continuously through monthly evaluations, juz promotion evaluations, five-juz milestone evaluations, and semester evaluations. The study concludes that the tahfidz education system at PPTQ Baitul Abidin Darussalam Wonosobo has been implemented in a structured and integrated manner, effectively supporting the achievement of tahfidz educational objectives in producing qualified Qur'an memorizers.